Environmental Surveillance as a Tool for Identifying High-risk Settings for Typhoid Transmission. (29th July 2020) - Andrews, Jason R; Yu, Alexander T; Saha, Senjuti; Shakya, Jivan; Aiemjoy, Kristen; Horng, Lily; Qamar, Farah; Garrett, Denise; Baker, Stephen; Saha, Samir; Luby, Stephen P
Abstract: Enteric fever remains a major cause of morbidity in developing countries with poor sanitation conditions that enable fecal contamination of water distribution systems. Historical evidence has shown that contamination of water systems used for household consumption or agriculture are key transmission routes for Salmonella Typhi and Salmonella Paratyphi A. The World Health Organization now recommends that typhoid conjugate vaccines (TCV) be used in settings with high typhoid incidence; consequently, governments face a challenge regarding how to prioritize typhoid against other emerging diseases. A key issue is the lack of typhoid burden data in many low- and middle-income countries where TCV could be deployed. Here we present an argument for utilizing environmental sampling for the surveillance of enteric fever organisms to provide data on community-level typhoid risk. Such an approach could complement traditional blood culture-based surveillance or even replace it in settings where population-based clinical surveillance is not feasible. We review historical studies characterizing the transmission of enteric fever organisms through sewage and water, discuss recent advances in the molecular detection of typhoidal Salmonella in the environment, and outline challenges and knowledge gaps that need to be addressed to establish environmental sampling as a tool for generating actionable data that can inform public health responses to enteric fever.